COMPARING COMMUNICATIVE TECHNIQUE WITH EXPLANATION TECHNIQUE IN TEACHING GRAMMAR - Haryanto Haryanto (Universitas Islam Nahdlatul Ulama Jepara, 2014)
ABSTRACT:There are some techniques of teaching grammar (English Grammar. Two of them are communicative and explanation techniques. Both communicative technique and explanation one can be used to present the materials likes poems, songs, poetry, map, and picture. Each has strength and weakness. By using communicative one the class becomes interesting and the student will not get bored. Whereas, by using the explanation one the student will get bored as well the teacher. However, it is the matter of the fact that based on the data of test result by the students, the result of explanation technique is better than communicative one.Key Words: Grammar, communicative, explanation, technique, teachingABSTRAK:Ada beberapa cara (teknik) pengajaran tata bahasa (English Grammar). Dua dianataranya adalah teknik komunikatif dan teknik penjelasan. Baik teknik komunikatif maupun penjelasan dapat digunakan untuk menyampaikan bahan tentang permainan, lagu, puisi, petadaan gambar. Masing-masing cara tadi memiliki kelemahan dan kelebihan Dengan teknik yang komunikatif kelas menjadi menyenangkan dan mahasiswa tidak bosan. Sedangkan dengan teknik menerangkan mahasiswa akan cepat merasa bosan, begitu juga dengan dosennya. Tetapi berdasarkan hasil data test mahasiswa, teknik menerangkan lebih bagus daripada teknik komunikatif.Kata kunci: Grammar, komunikatif, penjelasan, teknik, pengajaran